Company law - Dignam, Alan; Lowry, John (Butterworths core text series, 2012)
Company law is a popular company law textbook, providing an accessible writing style demystifying complex areas of law without over-simplification. This book focuses on key principles taught on undergraduate courses and explores corporate theory in some depth